Does Corporate Social Responsibility Moderate the Effect of Information Asymmetry and Earnings Management on Cost of Equity Capital? - Urna Fasihat, Dian; Iskandar, Rizkiana (Publisher Cv. Inara, 2024)
This study explores the relationship between information asymmetry, earnings management, Corporate Social Responsibility (CSR), and cost of equity capital (CEC). The results show that information asymmetry has a significant influence on CEC, which indicates that information uncertainty can increase the cost of equity capital of a company. On the other hand, earnings management practices have not been shown to have an effect on CECs, reflecting that investors may be more focused on long-term performance than short-term financial statement manipulation. In addition, CSR cannot moderate the influence of information asymmetry on CEC or the influence of earnings management on CEC.